Upcycling Walnut Green Husk: Polyphenol-Rich Extracts from Traditional Vs. Organic Crops for Spray-Dried Vegan Additive Development - Echeverria-Morgado, J; Matiacevich, S (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study explores the valorization of walnut green husk, an agro-industrial by-product, through ultrasound-assisted extraction to obtain polyphenol-rich extracts with antioxidant properties. The extracts demonstrated non-cytotoxicity, regardless of the presence of pesticides, antibiotics, or the type of crop. Notably, organic walnut husk yielded higher total polyphenols and antioxidant activity, identifying 37 polyphenolic compounds compared to 22 in traditional crops. Chickpea protein was utilized as a wall material to encapsulate the extract, resulting in a sustainable, vegan antioxidant powder. Optimal results were achieved using 5% (w/v) chickpea protein and spray drying at 136 degrees C, yielding a light-colored powder with high antioxidant content and stability under low humidity (<= 35%). The product shows promise as a natural, plant-based alternative to synthetic antioxidants in food systems. Further studies are needed to evaluate its functional and technological performance during food integration and storage.